COMMUNICATIVE APPROACH AS A KEY FACTOR IN MOTIVATING TECHNICAL COLLEGE STUDENTS TO LEARN ENGLISH (Ustozlar uchun, 2026)
This study investigates the effectiveness of the Communicative Language Teaching (CLT) approach in enhancing the motivation of English as a Foreign Language (EFL) learners at a technical college in Uzbekistan. The research was conducted at Chirchiq Technical College, involving 60 first-year students divided into control and experimental groups. A quasi-experimental design was employed over one academic semester. Data were collected through pre- and post-tests, motivation questionnaires, and classroom observation. Results indicate that students exposed to communicative activities demonstrated significantly higher motivation levels and improved oral communication skills compared to the control group. The findings suggest that integrating CLT methods into vocational English education contexts can substantially increase student engagement and learning outcomes.